2007
DOI: 10.1002/hed.20635
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients older than 75 years following major head and neck surgery

Abstract: Several QOL domains are decreased in elderly patients undergoing major head and neck surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Khafif et al also found no differences in overall QOL between patients aged 75 or older when compared with younger counterparts. 16 However, they did suggest some subdomains of QOL were adversely affected by advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…Khafif et al also found no differences in overall QOL between patients aged 75 or older when compared with younger counterparts. 16 However, they did suggest some subdomains of QOL were adversely affected by advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…To improve on these limitations, future studies could benefit from being prospective and having documented reasoning for including or excluding a patient from surgery. Incorporating QOL measures would also be beneficial, which could be compared with current QOL data . Using the Hopkins Frailty Score tool to see its predictive value in microsurgical outcomes would be of interest …”
Section: Discussionmentioning
confidence: 99%
“…5 Although more aggressive treatment provides gains in terms of locoregional control and disease recurrence, 7 it can also have a negative impact on vital organ functions and quality of life. [8][9][10] Moreover, patients with head and neck cancer often suffer from other alcohol-and tobacco related diseases, such as cardiac and respiratory illnesses, second primary tumours, hepatic or metabolic diseases, as well as cognitive disorders, 3,5,11 that may decrease their resilience, quality of life and treatment tolerance. 4,[11][12][13][14][15] As a result, older patients and those with comorbidity are often given a modified treatment in an attempt to avoid treatment-related complications and mortality.…”
Section: Introductionmentioning
confidence: 99%